Low doses effect in GaP light-emitting diodes - Hontaruk, O.M.; Konoreva, O.V.; Malyi, Ye.V.; Petrenko, I.V.; Pinkovska, M.B.; Radkevych, O.I.; Tartachnyk, V.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
The paper is devoted to the electrophysical characteristics study of serial red and green GaP light-emitting diodes (LEDs) irradiated with low α-particles doses (Φ ≤ 10¹² cm⁻²). It was stated that radiation features of p-n-junction and its capacitance change in dependence on temperature. The capacitance grows at 300 K, and drops at 77 K. At the same time, a direct branch of current-voltage characteristics shifts into the lower voltage direction, and appropriative barrier potential reduction value from 6.5 down to 3.5 eV is observed. The effects are caused by radiation defects, charge state of which depends on the Fermi level in GaP. The assumption has been made about high ionization level role in the sulfur impurity transition process into electrically active donor position.